2019
DOI: 10.1002/brb3.1246
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketogenic diet on behaviors and synaptic functions of naive mice

Abstract: Introduction Beyond its application as an epilepsy therapy, the ketogenic diet (KD) has been considered a potential treatment for a variety of other neurological and metabolic disorders. However, whether KD promotes functional restoration by reducing the pathological processes underlying individual diseases or through some independent mechanisms is not clear. Methods In this study, we evaluated the effect of KD on a series of behaviors and synaptic functions of young adult naive mice. Wild‐type C57BL/6J mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…In the study by Zhang et al (2018a, b), NAA, Cho, CR contents were assessed with MRI spectroscopy in animals fed a ketogenic diet after TBI. In addition, studies by Huang et al (2019) showed that KD applied for 3 months in mice did not cause changes in behavior when tested. But when the threshold for pentylenetetrazole-induced seizures was tested, it turned out to be higher in animals on KD.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Zhang et al (2018a, b), NAA, Cho, CR contents were assessed with MRI spectroscopy in animals fed a ketogenic diet after TBI. In addition, studies by Huang et al (2019) showed that KD applied for 3 months in mice did not cause changes in behavior when tested. But when the threshold for pentylenetetrazole-induced seizures was tested, it turned out to be higher in animals on KD.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical excitability was described as improved due to a reduction in long-term potentiation, without any change in baseline excitability or impact on normal brain activity. Not all studies noted reduced long-term potentiation (67) . 14.…”
Section: Alterations In Cellular Energetics and Metabolismmentioning
confidence: 99%
“…Diets were purchased from Research Diets, Inc (New Brunswick, NJ, USA). The control diet consisted of 10% protein, 80% carbohydrates and 10% fat, whereas ketogenic diet consisted of 10% protein and 90% fat [17]. All procedures involving animals were performed in accordance with protocols approved by Rutgers Biomedical and Health Sciences (Protocol Number: 999900700).…”
Section: Ketogenic Dietmentioning
confidence: 99%